In Vivo imaging of transgenic gene expression in individual retinal progenitors in chimeric Zebrafish embryos to study cell nonautonomous influences - Dudczig, Stefanie; Poggi, Lucia (JoVE. Video journal, 2017)
Live tracking of individual WT retinal progenitors in distinct genetic backgrounds allows for the assessment of the contribution of...